NOTARIES AS PARTIES IN CIVIL CASES BEFORE THE COURT - Anita Afriana (USU Journal of Legal Studies, 2017)
The role of a notary today is crucial for the parties who wish to make variety of agreements, due to authentic notarial deed is considered to be more secure for the society than the legal power of the deed under the hand. Nevertheless, in practice it is frequently discovered the presence of a notarial deed being sued to be requested for cancellation  before the court due to the fault of the parties who disagree and dihonest in his statement to the notary, or the fault of the notary him/herself, either for negligence or willful misconduct. This article / paper is an analytical descriptive study, in order to see the position of the notary in the process of examination of dispute in court either as a person in his/her capacity as a state official or from the positions of the authentic deed made are often the source of disputes and sanctions and responsibility of the notary who is deemed to have made mistakes during undertaking further work that is considered detrimental to the third party.  In terms of any problems that might arise in the future on the publication of an authentic deed made by the notary, the notary may not necessarily be drawn as the guilty party which caused the disputes, yet to be seen how far the offense has been committed by a notary, whether there is an error / not, a violation of the code of ethics and or the Law Number 2 of 2014 on the Position of Notary ( hereinafter referred to as UUJN ). In the dispute resolution in court on civil disputes, notaries can hold the position as the other party such as Defendant, if deemed to have committed an unlawful act to the detriment of others, as a co-defendant, or witness.